Ramona and her father - Cleary, Beverly; Tiegreen, Alan. (New York Scholastic, 1975)
The family routine is upset during Ramona's year in second grade when her father unexpectedly loses his job.
Newbery honor book--Cover.
Keywords: Fathers and daughters -- Fiction; Family problems -- Fiction